SLOPE EFFECT ON THE SEDIMENT PRODUCTION OF FOREST ROADS IN KASTAMONU OF TURKEY - Erdem, Ramazan; Enez, Korhan; Demir, Murat; Sariyildiz, Temel (Parlar Scientific Publications (P S P), 2018)
The purpose of this study was to determine actual amount of sediment productions of paved (PFR) and unpaved (UPFR) forest roads at different longitudinal slope groups (2-4%, 4-6%, 6-8%, 8-12%) were compared to undisturbed forest land (UA) in Kastamonu-Arac of Turkey with the help of the sediment traps. It was determinated that the total annual amount of sediments from the UPFR was found to be significantly higher than the amounts of sediments from the PFR and UA according to the slope groups. There were statistically significant differences between the amounts of sedimentation from the forest roads sides and within the UA (0.05<P). Annual sediment production of the sites was statistically different and determinated to 2098, 2485 and 5567 kg ha(-1) yr(-1) for UPFR (2-4%, 4-6%, 6-8%), 2522 kg ha(-1) yr(-1) PFR (8-12%) and 165, 179, 195, 169 kg ha(-1) UA (2-4%, 4-6%, 6-8%, 8-12%), respectively. Also, it was found that the total amount of sedimentation was in parallel to the monthly precipitation. It was observed that total sediment production across the study sites were less than the results of former researches. These differences may partly be explained by less traffic density (1-3 vehicles per day), not recently graded roads, lower logging and harvesting activities during research, and more plant cover in the current experimental sites. The obtained data will facilitate more effective application of the methods to stabilize the cutting slopes of a forest road.
Keywords: Kastamonu; Erosion; Forest Roads; Road cutslope; Arac; 15. Life on land